“Bosnian” Turkish and Its Authentic Features - Čau, Ekrem (Prilozi za orijentalnu filologiju, 2017)
Dialectologica! charaeteristics of Turkish dialects in the Balkans were formed during the complicated migration processes and under the strong influences of non-Turkish (manly Slavic) language substratum. These influences are especially visible in syntax. Apart from the large number of common char- acteristics which, generally speaking, can be identified as “Slavic”, it is indis- putable that each one of the dialects has its own charaeteristics based on the peculiarities of subsstratums throughout which the dialects continue to exist. Influences of Serbo-Croatian on “Bosriian” Turkish in matters of syntax are visible not only in the sentence word order but also in the process of conjunc- tionalization of Turkish pronouns, adverbs and adverbial expressions (specific calques (loan translations) of Serbo-Croatian conjunctions). After analysing these influences the author brings the following conclusions: a) Peculiarity of “Bosnian” dialect is that it was used by non-native (bilingual) speakers and that it was used by ethnically non-Turkish population of Bosnia as a mean of oral communication with Turkish and other non-Slavic subjeets of Otto- man Empire; b) For that reason the influence of native language, i.e. syntax of Serbo-Croatian language was more intensive; c) “Bosnian” dialect undoubtly was one of West Rumelian (Balkanian) dialects of Turkish language, and according to its syntactic charachteristics it could be called “Bosnian”, not only in sense of its geographycal determination, but also in sense of its variant-type determination.